2022
DOI: 10.3390/cancers14153785
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Deep Learning-Based Mitosis Recognition Approach and Dataset for Uterine Leiomyosarcoma Histopathology

Abstract: Uterine leiomyosarcoma (ULMS) is the most common sarcoma of the uterus, with both a high malignant potential and poor prognosis. Its diagnosis is sometimes challenging owing to its resemblance to leiomyosarcoma, often being accompanied by benign smooth muscle neoplasms of the uterus. Pathologists diagnose and grade leiomyosarcoma based on three biomarkers (i.e., mitosis count, necrosis, and nuclear atypia). Among these biomarkers, mitosis count is the most important and challenging biomarker. In general, patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A set of regression classifiers and machine learning models was defined for testing with this data set. Tests of statistical significance were carried out to check the validity of the result [51]. To do this, we evaluated the model 10 times and obtained the average values of accuracy and RMSE.…”
Section: Resultsmentioning
confidence: 99%
“…A set of regression classifiers and machine learning models was defined for testing with this data set. Tests of statistical significance were carried out to check the validity of the result [51]. To do this, we evaluated the model 10 times and obtained the average values of accuracy and RMSE.…”
Section: Resultsmentioning
confidence: 99%
“…AI is one of the cutting-edge technologies of Industrial Revolution (IR) 4.0, which has been adopted in all aspects of life, such as health, transportation, construction, security, sports, etc. , Data set preparation is one of the crucial steps while working with ML- and DL-related problems. However, obtaining the labeled data set from an open source is still challenging in many domains, including semiconductors.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, AI has played a positive role in complex pattern recognition and solving real-world problems. , After the emergence of machine learning (ML) and deep learning (DL), researchers have employed these technologies in various fields such as healthcare, , construction, bioinformatics, finance, , and agriculture . In the field of nanomaterials science, researchers have started to employ AI-based DL and ML technology for RHEED interpretation, such as employing statistically available methods with ML for RHEED interpretation. , For instance, authors used principal component analysis (PCA) and k -means clustering to analyze different types of perovskite films to understand their stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…A higher mitotic index is associated with aggressive tumor behavior, including recurrence and distant metastasis, leading to a poorer prognosis. Studies have shown that AI algorithms could successfully count the mitosis of tumor cells for neuroendocrine tumor, invasive breast carcinoma, and leiomyosarcoma [ 41 42 43 ]; however, its effectiveness in GIST has not yet been demonstrated. As the morphology of mitotic figures is similar across different tumor types, similar AI models could be applied to GIST.…”
Section: Detecting Basic Histologic Components and Diagnosismentioning
confidence: 99%